The role of Pancasila ideology in legitimizing public policies during the COVID-19 pandemic in Indonesia - Supramudyo, Gitadi Tegas; Irianto, Jusuf; Setijaningrum, Erna; Bahar, Adam Amin (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
The national ideology is often utilized as a tool to legitimize governmental actions. This study seeks to examine how government elites use the Pancasila ideology to legitimize public policies in the era of the COVID-19 pandemic. Employing a grounded reflective interpretive methodological approach within the framework of postfoundational discourse, this study shows that several controversial policies implemented during the COVID-19 pandemic tended to be bolstered and justified by their alignment with the Pancasila ideology. These endeavors are chiefly undertaken by governmental actors who espouse these policies. Representing the ruling regime, these government actors consistently assert adherence to the fundamental tenets of Pancasila or self-identify as the most